Ética em gestão escolar: fundamentos para uma práxis educativa - Natal, Mariene do Nascimento (2017)
The present study subject is the management ethical basis in public schools at São Paulo state. Considering the cultural and political spheres of public educational institutions, it is assumed that school managers have an ethics commitment, which guides educational principles, strategies and decisions. There is the purpose to find, in the field of ethics, the basis for a management practice that will be able to know and to give value to diversity, as a possibility for the school to become an educational community, and that assumes the status of a public institution, as synonymous with commitment to the common interest. Bibliographical research, study of legal documents and interviews with masters and educational coordinators teachers are taking to identify the concerning ethic to the social and political responsibility of public schools, through the dialectical perspective of the philosophy of praxis. The analysis points to the concepts of organic intellectual work and public interest as a direction to management praxis.